Correction: pH and reduction-activated polymeric prodrug nanoparticles based on a 6-thioguanine-dialdehyde sodium alginate conjugate for enhanced intracellular drug release in leukemia. Issue 24 (6th June 2018) - Wan, Yanming; Bu, Ying; Liu, Jiaming; Yang, Jia; Cai, Weiquan; Yin, Yihua; Xu, Wenjin; Xu, Peihu; Zhang, Jingli; He, Meng
Abstract : Correction for 'pH and reduction-activated polymeric prodrug nanoparticles based on a 6-thioguanine-dialdehyde sodium alginate conjugate for enhanced intracellular drug release in leukemia' by Yanming Wan et al., Polym. Chem., 2018, DOI: 10.1039/c8py00577j.